The way of the Tempted Jesus as the Basis for Understanding the Pilgrimage of the Church - Nguyen Ngoc Khang, (Archīum Ateneo, 2019)
This research project is a collection of four major papers in the field of systematic theology. The first paper discusses the temptation of Jesus in Matthew's Gospel. Jesus' temptations can be seen as the first sign of salvation. In his baptism, Jesus inaugurates the renewal of the people of God. In his temptation, Jesus actualizes this renewal by presenting his basic orientation of life as the new way for God's people. The second paper explores the Church as a Pilgrim People. It presents Church's pilgrimage as being initiated by God's summon, unfolded in the historical drama of Israel, and fulfilled in Jesus Christ as the perfect leader and model. This pilgrimage indicates the ongoing conversion of the Church in becoming a sign and instrument of God's love to the world. The third paper addresses contemporary reflection on the doctrine of original sin, especially in light of modern challenges against the teaching. Concerning the first challenge on the historical reading of Gen 2-3, the response is to return to the level of the Church's confession. Concerning the challenges on the existence of Adam and the aftermath of his falling, the responses are the evolutionary approach and the psychological-existential-social approach. The fourth paper deals with the moral dilemma involving conjoined twins. This case relates to various principles of2morality, such as the sanctity of life, bodily integrity, the principle of double effect and so on. Yet the informed conscience of the parents has to have the first priority in assessing this case. Although these major papers refer to separate topics, they can be put together under the theme, "The temptation Jesus as a basis for understanding the pilgrimage of the Church." The temptation of Jesus sheds light on the pilgrimage of the Church in its limitation and potential. Such limitation and potential may be recognized in the Church's teaching on original sin and moral dilemmas.